Does Low Grade Systemic Inflammation Have a Role in Chronic Pain? - Zhou, Wen Bo Sam; Meng, JingWen; Zhang, Ji (Frontiers in Molecular Neuroscience, 2021)
One of the major clinical manifestations of peripheral neuropathy, either resulted from trauma or diseases, is chronic pain. While it significantly impacts patients’ quality of life, underlying mechanisms remain elusive, and treatment is not satisfactory. Systemic chronic inflammation (SCI) that we are referring in the perspective, is a state of low-grade, persistent, non-infective inflammation, being found in many physiological and pathological conditions. Distinct from acute inflammation, which is a protective process fighting against intruders, SCI might have harmful effects. It has been associated with many chronic non-communicable diseases. We hypothesize that SCI could be a predisposing and/or precipitating factor in the development of chronic pain, as well as associated comorbidities. We reviewed evidence from human clinical studies indicating the coexistence of SCI with various types of chronic pain. We also collated existing data about the sources of SCI and who could have it, showing that those individuals or patients having SCI usually have higher prevalence of chronic pain and psychological comorbidities. We thus elaborate on the need for further research in the connection between SCI and chronic pain. Several hypotheses have been proposed to explain these complex interactions.